Biomechanics and physiology of uphill and downhill running - Vernillo, G.; Giandolini, M.; Edwards, W. B.; Morin, J.-B.; Samozino, P.; Horvais, N.; Millet, G. Y. (Sports Medicine, 2017)
Most running studies have considered level running (LR), yet the regulation of locomotor behaviour during uphill (UR) and downhill (DR) running is fundamental to increase our understanding of human locomotion. The purpose of this article was to review the existing literature regarding biomechanical, neuromuscular and physiological adaptations during graded running. Relative to LR, UR is characterized by a higher step frequency, increased internal mechanical work, shorter swing/aerial phase duration, and greater duty factor, while DR is characterized by increased aerial time, reduced step frequency and decreased duty factor. Grade also modifies foot strike patterns, with a progressive adoption of a mid- to fore-foot strike pattern during UR, and rear-foot strike patterns during DR. In UR, lower limb muscles perform a higher net mechanical work compared to LR and DR to increase the body`s potential energy. In DR, energy dissipation is generally prevalent compared to energy generation. The increased demands for work as running incline increases are met by an increase in power output at all joints, particularly the hip. This implies that UR requires greater muscular activity compared to LR and DR. Energy cost of running (Cr) linearly increases with positive slope but Cr of DR decreases until a minimum slope is reached at -20 %, after which Cr increases again. The effects of slope on biomechanics, muscle contraction patterns and physiological responses have important implications for injury prevention and success of athletes engaged in graded running competitions.